HUMAN CAPITAL AS A DEVELOPMENT FACTOR OF ORGANIC AGRICULTURE IN THE REPUBLIC OF SERBIA - Tomaš Simin, Mirela; Glavaš-Trbić, Danica; Milić, Dragan; Janković, Dejan (Economics of Agriculture, 2024)
Authors explore the role of human capital in organic agriculture in Serbia. Through semi-structured interviews with 64 individual farmers holding organic production certificates, key aspects of human capital, including education level, language proficiency and ICT usage were analyzed. Findings reveal a disparity between conventional and organic farming in terms of computer literacy and ICT utilization, underscoring the need for targeted interventions to enhance technological adoption in organic farming. Moreover, the study identifies the importance of membership in agricultural associations for organic farmers, facilitating knowledge exchange and market penetration. The results suggest that human capital plays a pivotal role in driving advancements in organic agriculture, with implications for the sustainability and growth of the sector in Serbia. This underscores the necessity for future research to go deeper into human capital dynamics and their implications for sustainable agricultural development.